Das Ständehaus in Düsseldorf : Die Kunstsammlung Nordrhein-Westfalen im Ständehaus 1875-2002. - K21 Kunstsammlung Nordrhein-Westfalen Düsseldorf; Ständehaus Düsseldorf; Clement, Wolfgang; Düwell, Kurt; Garske, Erhard; Grün, Ingo; Kiessler, Uwe; Köstler, Andreas; Munsch, Jörg; Schmidt, Ulrich; Tönnesmann, Andreas; Vesper, Michael; et al. (Köln : DuMont Literatur und Kunst Verlag, 2002)
Byars, James Lee ; Chin, Mel ; Fritsch, Katharina ; Gala Committee ; Honert, Martin ; Kabakov, Ilya ; Kawara, On ; Kippenberger, Martin ; Knoebel, Imi ; Kounellis, Jannis ; Levine, Sherrie ; Muñoz, Juan ; Pistoletto, Michelangelo ; Polke, Sigmar ; Ruff, Thomas ; Schütte, Thomas ; Struth, Thomas ; Wall, Jeff
Duits
boek